Operations Management - Schiraldi, Massimiliano M. (IntechOpen, 2013)
Operations Management is an area of business concerned with managing the process that converts inputs into outputs, in the form of goods and/or services. Increasingly complex environments together with the recent economic swings and substantially squeezed industrial margins put extra pressure on companies, and decision makers are pushed to increase operations efficiency and effectiveness. This book presents the contributions of a selected group of researchers, reporting new ideas, original results and practical experiences as well as systematizing some fundamental topics in Operations Management. Although it represents only a small sample of the research activity on Operations Management, people from diverse backgrounds, academia, industry and research as well as engineering students can take advantage of this volume.